Floating with Kim Scott's Benang: Vertigo, settler-colonial mobilities and levitation's geographies. (August 2021) - Adey, Peter
Abstract: In this paper I explore the strange figure of the levitator within Kim Scott's (1999) Miles Franklin Prize winning novel Benang: From the Heart . Through different genres of art and creative practice, mysticism, religion, science-fiction, magic, and even civil disobedience, the levitator is a poorly acknowledged mobile subject who seems to refuse scholarly enquiry. Levitation is more readily understood as a maligned form of fraud, fakery and social frippery, a figure of esoteric interest. Building on recent attempts to resurrect and reconsider levitators (Adey, 2017; Young, 2018), as well as floating, lighter-than-air atmospheres and elements (McCormack, 2018; Engelmann, 2015), this paper argues that floatations like levitation provide a crucial addition to critical and radical thinking in mobilities, affective life and studies of settler-colonialism. Through Benang, Kim Scott's vast historical and yet intimate novel, the paper works with the floating encounters woven through the politics and ecologies of Western Australia and its racist policies which sought to regulate the Noongar people, an Aboriginal people recognised as the traditional owners of south west Western Australia. Within Benang, levitation, lightness and detachment, become expressions of vertiginous (post)colonial distance, fear, anxiety and escape. Highlights: This paper explores the strange figure of the levitator within Kim Scott's (1999) Miles Franklin Prize winning novel Benang: From the Heart . The paper argues that floatations like levitation provide a crucial addition to critical and radical thinking in mobilities, affective life and studies of settler-colonialism. Levitation is examined as an expression of vertiginous (post)colonial distance, fear, anxiety and escape.